The study of chromium oxide loading on platinum chromium oxide zirconia catalyst for n-dodecane and 1,4-diisopropylbenzene hydrocracking - N. H. R., Annuar; L. P., Teh; H. D., Setiabudi; M. A. A., Aziz; N. M., Salam; A. A., Abdul Jalil (Institute of Physics Publishing, 2020)
Hydrocracking reaction is one of the major processes in petroleum refining. To date, the exploration of a suitable catalyst for hydrocracking reaction remains challenging. The presence of Pt loaded on Cr2O3-ZrO2 promotes the catalytic activity and stability of Cr2O3-ZrO2. While, zirconia has an interesting thermal and mechanical properties which make it as a support material. Therefore, in this study, platinum chromium oxide zirconia catalyst (Pt/Cr2O3-ZrO2) with different Cr2O3 loading (1, 4, 8, and 12 wt%) were prepared by impregnation method. The physical and chemical properties will be characterized by the XRD and FTIR analysis whereas catalytic testing will be analyzed by n-dodecane and 1,4-diisoproylbenzene hydrocracking. The XRD results showed that the peak intensity of the tetragonal phase of ZrO2 and bulk crystalline of Cr2O3 increased with the increase in the Cr2O3 loading from 1 to 12 wt%. The FTIR KBr analysis showed the presence of monoclinic and tetragonal phase of ZrO2 and none or only negligible amount of coke formed during the reaction. The 2,6-lutidine adsorbed FTIR analysis showed that six bands located at 1675, 1660, 1650, 1640, 1630 and 1625 cm-1 corresponding to the Bransted acid sites whereas the Lewis acid sites located at 1608, 1603, 1593, 1580, 1565 and 1560 cm-1. For n-dodecane and 1,4-diisoproylbenzene hydrocracking, all catalysts showed 100% conversion except for Pt/12Cr2O3-ZrO2. Hence, the presence of tetragonal phase and Lewis acid sites play an important role for catalytic activity of n-dodecane and 1,4-diisoproylbenzene hydrocracking.